PENGEMBANGAN RANCANGAN PEMBELAJARAN BERBASIS HIGHER ORDER THINKING SKILL (HOTS) DALAM KURIKULUM 2013 PENDIDIKAN AGAMA HINDU - Ni Made Surawati; Dewa Kadek Sudyana (UNHI PRESS, 2019)
Higher Order Thinking Skills (HOTS) is a way of thinking that puts forward the values ​​of critical and creative thinking so that it is considered capable of providing solutions in facing the challenges of the times. To have high-level thinking skills (HOTS), teachers must be able to design HOTS-based learning to help students develop higher-order thinking skills. The ability in question is related to the ability to think critically, reflective, metacognitive, and creative thinking. This is consistent with the objectives in the 2013 curriculum in PP No. 17 of 2010, to prepare Indonesian people to have the ability to live as individuals and citizens who are faithful, productive, creative, innovative, and affective and able to contribute to the life of society, nation, state and world civilization